Bisoprolol Transdermal Patch Is Effective for the Treatment of AF Tachycardia - Yoh Arita; Hajime Saeki; Miwa Miyoshi; Shinji Hasegawa (Case Reports in Cardiology)
Atrial fibrillation (AF) is an irregular and often rapid heart rate that can increase the risk of stroke, heart failure, and other heart-related complications. Its incidence increases with age and the presence of concomitant heart disease. We present the cases of a 93-year-old woman, an 82-year-old man, and an 87-year-old woman who developed AF tachycardia. This report highlights the use of a bisoprolol transdermal patch to treat AF tachycardia in 3 adult elderly patients. In this paper, we report an initial treatment strategy using a bisoprolol transdermal patch and show heart rate trends for 24 hours.